2015
DOI: 10.1093/nar/gkv1348
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α4β1 controls G9a activity that regulates epigenetic changes and nuclear properties required for lymphocyte migration

Abstract: The mechanical properties of the cell nucleus change to allow cells to migrate, but how chromatin modifications contribute to nuclear deformability has not been defined. Here, we demonstrate that a major factor in this process involves epigenetic changes that underpin nuclear structure. We investigated the link between cell adhesion and epigenetic changes in T-cells, and demonstrate that T-cell adhesion to VCAM1 via α4β1 integrin drives histone H3 methylation (H3K9me2/3) through the methyltransferase G9a. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 56 publications
3
34
0
Order By: Relevance
“…It has been suggested that mechanoadaptation of the chromatin occurs faster than nuclear lamina alterations [13,20]. Aligning with these studies, we have previously described that epigenetic changes related with closed chromatin conformation alter the mechanical properties and shape of nuclei from lymphocytes and leukemia cells [21]. Now, we have extended these results and described how increased levels of a euchromatin marker (H3K4 methylation) are linked to the biomechanical properties of isolated nuclei from cells moving in 3D environments [22].…”
Section: Chromatin Contribution To Nuclear Stiffnesssupporting
confidence: 61%
“…It has been suggested that mechanoadaptation of the chromatin occurs faster than nuclear lamina alterations [13,20]. Aligning with these studies, we have previously described that epigenetic changes related with closed chromatin conformation alter the mechanical properties and shape of nuclei from lymphocytes and leukemia cells [21]. Now, we have extended these results and described how increased levels of a euchromatin marker (H3K4 methylation) are linked to the biomechanical properties of isolated nuclei from cells moving in 3D environments [22].…”
Section: Chromatin Contribution To Nuclear Stiffnesssupporting
confidence: 61%
“…Previous studies on various integrins highlight that, in addition to adhesion, these receptors regulate cell migration, proliferation, cell-fate determination, cell cycle progression, apoptosis prevention, and cell survival and differentiation in diverse cell types (71)(72)(73)(74)(75)(76)(77). Binding of activated integrins to their ligands results in a number of signaling, structural, and phenotypic changes within the cell.…”
Section: Integrin's Functions Beyond Cell Adhesionmentioning
confidence: 99%
“…Several multiprotein complexes assemble onto integrins' cytoplasmic tails to engage and reorganize the cytoskeletal systems, as well as to facilitate the transmission of signaling cascades that ultimately lead to changes in the expression of certain genes. For example, VLA-4 regulates G9a activity that controls epigenetic changes and the nuclear properties that are required for lymphocyte migration (73). In mammary epithelium, b 1 integrin plays a major role in controlling differentiation and development, as well as in the cellular programming of epithelial functions (74,75).…”
Section: Integrin's Functions Beyond Cell Adhesionmentioning
confidence: 99%
“…Epigenetic modifications, which include covalent changes in histones and DNA, regulate chromatin structure and gene expression (12). Some histone markers have been related to cancer progression and cell migration (13)(14)(15). The histone H3 is methylated at the residue K4 by specific methyltransferase complexes, which comprise a catalytic subunit (SET/MLL) and several core scaffolding subunits, including WDR5 (WD repeat-containing protein 5), ASH2L, RbBP5, and mDPY-30 (16).…”
Section: Introductionmentioning
confidence: 99%